2020
DOI: 10.28991/cej-2020-03091558
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Numerical Evaluation of Concentrically Loaded RC Columns Strengthening by Textile Reinforced Concrete Jacketing

Abstract: Nowadays, Textile Reinforced Concrete (TRC) has become a very popular strengthening technique for concrete structures. This paper presents an investigation on the applicability of TRC for strengthening reinforced concrete column. Both experimental and numerical studies are conducted to evaluate the confinement effects of various TRC strengthening schemes. The experimental study is performed on a series of six reinforced concrete square columns tested to failure. Two of them were un-strengthened as references, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…At the corners of the columns, the tensile strength of the textile reinforcements was reduced due to the curvature of the textile rovings and the effect of the complex stresses. The tensile strength of carbon textiles at the corner regions was suggested to be 900 MPa by Ngo et al [7]. Some parameters of the ordinary concrete and fine-grained concrete are presented in Table 2.…”
Section: Modeling Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…At the corners of the columns, the tensile strength of the textile reinforcements was reduced due to the curvature of the textile rovings and the effect of the complex stresses. The tensile strength of carbon textiles at the corner regions was suggested to be 900 MPa by Ngo et al [7]. Some parameters of the ordinary concrete and fine-grained concrete are presented in Table 2.…”
Section: Modeling Techniquesmentioning
confidence: 99%
“…The authors also noted that increasing the number of textile mesh layers can further enhance the compressive strength of the column. In a study by Ngo et al [7], carbon TRC was used to reinforce six columns with a length of 800 mm and a crosssectional size of 200 x 200 mm. The results of axial compression tests indicated that using carbon textiles increases the ductility and compressive strength of the RC columns.…”
Section: Introductionmentioning
confidence: 99%
“…The results also shown that ECC itself could be used as a new retrofitting material in column confinement. The experimental study is performed on a series of six reinforced concrete square columns tested to failure by Ngo et al (2020) [39]. Two of them were un-strengthened as references, the other four were strengthened by one or two layers of Carbon Textile Reinforced Concrete (CTRC).…”
Section: Introductionmentioning
confidence: 99%
“…More details on the performance of steel angles, steel jackets, and ferro-cement jackets can be found in the state-of-the-art review by Raza et al [22] and Kaish et al [23]. Recently, the uses of fibrous jackets, textile-reinforced concrete jackets, and prestressed steel jackets to strengthen RC structures were demonstrated by Jassim and Chassib [24], Ngo et al [25], and Sirimontree et al [26], respectively, The performance of RC circular and square columns under cyclic loading were examined by Ahmed et. al.…”
Section: Introductionmentioning
confidence: 99%